IMPLEMENTASI KEBIJAKAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA DI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS TADULAKO - Juniar, Fira; Tawil, Muzakir; Sri Astuti, Agusta (JPS: Journal of Publicness Studies, 2024)
The Government of the Republic of Indonesia issued a policy related to the Independent Campus Learning Program which is regulated through Permedikbud Number 3 of 2020 concerning National Higher Education Standards. in this case, this policy contains the right of students to carry out learning outside the study program for a maximum of three semesters with the aim that students can get the opportunity to broaden their horizons, experience, and improve competencies according to their interests, talents and ideals. This program is expected to be the answer to the demands of the current times. The purpose of this study is to determine the extent to which this policy is implemented. Qualitative descriptive method is used in this research, where the analysis is carried out on the data that has been collected both from documents, journals, observations, interviews which are then analyzed and described systematically in accordance with the formulation of existing problems, analyzed by George C. Edward III's theory with four aspects consisting of communication, resources, disposition, and bureaucratic structure. The research results obtained show that the implementation of the Merdeka Learning Campus Merdeka program policy at the Faculty of Social and Political Sciences, Tadulako University has not gone well. This is because there are still several obstacles in implementing the policy. The implementing party is required to increase the consistency of towards the implementation of 8 types of MBKM program activities, it is still necessary to conduct a type of socialization or coordination meeting between the implementing parties at the faculty level through monitoring meetings and also evaluating the implementation of activities, the unavailability of supporting facilities such as the MBKM FISIP room, capacity building related to the understanding of lecturers in several study programs. Then, related to the attitude of the implementers in this case, if there are MBKM program activities that are deemed irrelevant to the original study program, it is necessary to provide other alternatives such as courses related to the MBKM program that students follow. Furthermore, in the bureaucratic structure, although the distribution of structures and responsibilities has been well distributed, monitoring and evaluation of the implementation of the MBKM program at the Faculty of Social and Political Sciences, Tadulako University must still be carried out.